Role of Vitamin B-12 in chronic low backache: A comparative study - Ali, Syed Danish; Shah, Syed Kamran Ali; Qureshi, Muhammad Kamran; Akram Muhammad Aliuddin; Ali, Ahmed; Siddiqui, Aslam (International Journal of Endorsing Health Science Research, 2021)
Background: Chronic low backache is a commonly affecting problem in our population; it has an economic impact due to the consumption of health expenses in its treatment and rehabilitation. Backache interferes with daily activities of life without discriminating age, gender or race, etc. Our study aimed to determine the role of vitamin B-12 in relieving chronic low backache. Methodology: A comparative study was conducted at Baqai University and Fatima Hospital, Karachi, from May 2019 to April 2020. A total of 496 patients were enrolled and divided into two groups; group I was treated with vitamin B-12 (n=256), and group II (n=240) did not receive vitamin B-12 treatment. Pre-treatment Visual Analog Scale (VAS) score and Oswestry Disability Index (ODI) scores were evaluated. Group II was given calcium supplements and Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) for one month, while group I was given intramuscular injections of vitamin B-12 (500 mcg) on an alternate day for a month along with calcium supplements and NSAIDs. Results: Pre-treatment mean VAS and ODI scores were 6.68 ± 1.45 and 30.11 ± 12.7, while post-treatment VAS and ODI scores were subsequently 3.50 ± 2.07 and 17.73 ± 12.7, respectively. At the end of treatment, a remarkable decrease in ODI and VAS scores was observed after treatment with vitamin B-12 (p<0.05). Conclusion: Concurrent use of vitamin B-12 in the treatment of chronic backache had a better impact in relieving backache symptoms than those treated without vitamin B-12.